2010
DOI: 10.1002/stem.533
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of XIAP Combined with Systemic Mesenchymal Stem Cell-Mediated Delivery of sTRAIL Ligand Inhibits Metastatic Growth of Pancreatic Carcinoma Cells

Abstract: Disseminating tumors are one of the gravest medical problems. Here, we combine the tumor-specific apoptosis-inducing activity of tumor necrosis factor-related apoptosisinducing ligand (TRAIL) with the ability of mesenchymal stem cells (MSCs) to infiltrate both tumor and lymphatic tissues to target primary tumors as well as disseminated cancer cells in a human pancreatic cancer mouse model. Furthermore, we targeted X-linked inhibitor of apoptosis protein (XIAP) by RNA interference (RNAi) inside the cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 53 publications
(74 reference statements)
3
70
0
Order By: Relevance
“…23 MSCs expressing and secreting tumor necrosis factor-related apoptosis-inducing ligand using systemic MSC-mediated delivery were shown to suppress metastatic growth of pancreatic carcinoma. 24 Furthermore, Toro et al have shown an efficient treatment of the metastatic dissemination of the ovarian tumor by yCD-UPRT gene-modified AT-MSCs in nude mouse model. 25 The authors did not consider existence of MSC-exosomes with suicide gene mRNA; therefore, the explanation was linked to the bystander effect.…”
Section: Discussionmentioning
confidence: 99%
“…23 MSCs expressing and secreting tumor necrosis factor-related apoptosis-inducing ligand using systemic MSC-mediated delivery were shown to suppress metastatic growth of pancreatic carcinoma. 24 Furthermore, Toro et al have shown an efficient treatment of the metastatic dissemination of the ovarian tumor by yCD-UPRT gene-modified AT-MSCs in nude mouse model. 25 The authors did not consider existence of MSC-exosomes with suicide gene mRNA; therefore, the explanation was linked to the bystander effect.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Increased number of MSC-mediated anticancer studies have shown MSCs to be an effective therapeutic tool and gene carrier for the treatment of pancreatic cancer. 34 To use MSCs as effective anticancer agent vehicles, we need a viable and practical source of MSCs and a method to successfully transfect MSCs with anticancer genes. To this end, we have successfully isolated and characterized MSCs from the ductal tissue of human donor pancreases and as well as, we have successfully transfected and expressed TRAIL in MSCs.…”
Section: Dynamic Observation Of Msc Migration Toward Pancreatic Cancementioning
confidence: 99%
“…We have also designed additional supplementary treatments, like microRNA-21 (miR-21) inhibitors [139] and novel PI3-kinase/mTOR inhibitor, PI-103 [140] to augment the antitumor effect of different stem cell-mediated S-TRAIL therapy in vivo. A similar study has demonstrated that the combined approach using systemic MSC-mediated delivery of TRAIL together with XIAP inhibition suppresses metastatic growth of pancreatic carcinomas [141]. These findings offer a preclinical rationale for application of mechanism-based systemically delivered anti-proliferative agents and novel stem cell-based proapoptotic therapies to improve treatment of malignant tumors.…”
Section: Synergistic Approaches Utilizing Msc-based Therapeutics Withmentioning
confidence: 90%